2021
DOI: 10.3390/ijms222312945
|View full text |Cite
|
Sign up to set email alerts
|

Role of ANGPTL8 in NAFLD Improvement after Bariatric Surgery in Experimental and Human Obesity

Abstract: Angiopoietin-like protein 8 (ANGPTL8) is an hepatokine altered in several metabolic conditions, such as obesity, type 2 diabetes, dyslipidemia and nonalcoholic fatty liver disease (NAFLD). We sought to explore whether ANGPTL8 is involved in NAFLD amelioration after bariatric surgery in experimental models and patients with severe obesity. Plasma ANGPTL8 was measured in 170 individuals before and 6 months after bariatric surgery. Hepatic ANGPTL8 expression was evaluated in liver biopsies of patients with severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Both SG and RYGB induce the downregulation of angiopoietin-like 8 (ANGPTL8), which inhibits lipogenesis in human hepatocytes when exposed to lipotoxic conditions and is associated with the degree of steatosis in the livers of rats with diet-induced obesity. These findings support the suppose that ANGPTL8 partly improves NAFLD after BS by improving hepatic lipid metabolism ( Perdomo et al, 2021 ). Bile acid signaling also contributes to the resolution of NAFLD after BS, as RYGB causes an increase in total BAs, and this is related to the normalized accumulation of liver fat.…”
Section: Bariatric Surgery and Non-alcoholic Fatty Liver Diseasesupporting
confidence: 88%
“…Both SG and RYGB induce the downregulation of angiopoietin-like 8 (ANGPTL8), which inhibits lipogenesis in human hepatocytes when exposed to lipotoxic conditions and is associated with the degree of steatosis in the livers of rats with diet-induced obesity. These findings support the suppose that ANGPTL8 partly improves NAFLD after BS by improving hepatic lipid metabolism ( Perdomo et al, 2021 ). Bile acid signaling also contributes to the resolution of NAFLD after BS, as RYGB causes an increase in total BAs, and this is related to the normalized accumulation of liver fat.…”
Section: Bariatric Surgery and Non-alcoholic Fatty Liver Diseasesupporting
confidence: 88%
“…Betatrophin (ANGPLT8) is the most recently identified member of the ANGPLT proteins, expressed primarily in the liver [17]. Betatrophin acts as a hepatokine in an autocrine/paracrine manner, decreasing intracellular triglyceride content of hepatocytes through the downregulation of lipogenic transcription factors [4]. Former studies reported that higher serum betatrophin levels are associated with insulin resistance in T2D patients [11][12][13]18].…”
Section: Discussionmentioning
confidence: 99%
“…Betatrophin shares homology with other members of the ANGPTL family, especially with angiopoietin-like protein 3 (ANGPLT3)'s N-terminal domain, which regulates blood lipids, and with angiopoietin-like protein 4 (ANGPLT4)'s N-terminal segment, which mediates LPL binding [1]. Previous studies demonstrated increased concentrations of betatrophin in metabolic diseases associated with lipid disorders, such as dyslipidemia [3] and non-alcoholic fatty liver disease [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are contrasting findings regarding ANGPTL8 concentrations following bariatric surgery, with some studies reporting higher levels. Conversely, higher levels of ANGPTL8 expression in the blood and liver are associated with various stages of NAFLD [ 13 ]. Although studies have found that blood ANGPTL8 levels are higher in NAFLD patients [ 14 ], the correlation between ANGPTL8 and the lipid profile in the etiopathogenesis of NAFLD remains unexplained.…”
Section: Introductionmentioning
confidence: 99%